Solvent tuning of the substitution behavior of a seven-coordinate iron(III) complex - Ivanovic-Burmazovic, Ivana; Hamza, Mohamed; van Eldik, Rudi (Inorganic Chemistry, 2006)
A detailed kinetic study of the substitution behavior of the seven-coordinate [Fe(dapsox)(L)]ClO complex (H -dapsox = 2,6-diacetylpyridine-bis(semioxamazide), L = solvent or its deprotonated form) with thiocyanate as a function of the thiocyanate concentration, temperature, and pressure was undertaken in protic (EtOH and acidified EtOH and MeOH) and aprotic (DMSO) organic solvents. The lability and substitution mechanism depend strongly on the selected solvent (i.e., on solvolytic and protolytic processes). In the case of alcoholic solutions, substitution of both solvent molecules by thiocyanate could be observed, whereas in DMSO only one substitution step occurred. For both substitution steps, [Fe(dapsox)(L)]ClO shows similar mechanistic behavior in methanol and ethanol, which is best reflected by the values of the activation volumes (MeOH ΔV = +15.0 ± 0.3 cm mol, ΔV = +12.0 ± 0.2 cm mol; EtOH ΔV = +15.8 ± 0.7 cm mol, ΔV = +11.1 ± 0.5 cm mol ). On the basis of the reported activation parameters, a dissociative (D) mechanism for the first substitution step and a D or dissociative interchange (I) mechanism for the second substitution step are suggested for the reaction in MeOH and EtOH. This is consistent with the predominant existence of alcoxo [Fe(dapsox)(ROH)(OR)] species in alcoholic solutions. In comparison, the activation parameters for the substitution of the aqua-hydroxo [Fe(dapsox)(HO)(OH)] complex by thiocyanate at pH 5.1 in MES were determined to be ΔH = 72 ± 3 kJ mol , ΔS = +38 ± 11 J K mol, and ΔV = -3.0 ± 0.1 cm mol, and the operation of a dissociative interchange mechanism was suggested, taking the effect of pressure on the employed buffer into account. The addition of triflic acid to the alcoholic solutions ([HOTf] = 10 and 10 M to MeOH and EtOH, respectively) resulted in a drastic changeover in mechanism for the first substitution step, for which an associative interchange (I) mechanism is suggested, on the basis of the activation parameters obtained for both the forward and reverse reactions and the corresponding volume profile. The second substitution step remained to proceed through an I or D mechanism (acidified MeOH ΔV = +9.2 ± 0.2 cm mol ; acidified EtOH ΔV = +10.2 ± 0.2 cm mol). The first substitution reaction in DMSO was found to be slowed by several orders of magnitude and to follow an associative interchange mechanism (ΔS = -50 ± 9 J K mol, ΔV = -1.0 ± 0.5 cm mol), making DMSO a suitable solvent for monitoring substitution processes that are extremely fast in aqueous solution. © 2006 American Chemical Society.